Platelet-induced growth of human fibroblasts is associated with an increased expression of 5-lipoxygenase - Berg, Cecilia; Hammarström, Sven; Herbertsson, Helena; Lindström, Eva; Svensson, Ann-Charlotte; Söderström, Mats; Tengvall, Pentti; Bengtsson, Torbjörn (Thrombosis and Haemostasis, 2006)
Proliferation of fibroblasts is vital for adequate wound healing but is probably also involved in different hyperproliferative disorders such as atherosclerosis and cancer. The regeneration of tissue usually starts with coagulation, involving release of mitogenic and inflammatory factors from activated platelets. This study focuses on the role of eicosanoids in the proliferative effects of platelets on human fibroblasts. We show that the phospholipase A2 inhibitor 7,7-dimethyl-5,8-eicosadienoic acid (DMDA), the combined cyclooxygenase (COX) and lipoxygenase (LOX) inhibitor 5,8,11,14-eicosatetraynoic acid (ETYA) and the LOX inhibitor 5,8,11-eicosatriynoic acid (ETI) block the platelet-induced proliferation of serum starved subconfluent human fibroblasts. Anti-proliferative effects were also obtained by specific inhibition of 5-LOX with 5,6-dehydro arachidonic acid (5,6-dAA), whereas the 12-LOX inhibitor cinnamyl-3,4-dihydroxy-α-cyanocinnamate (CDC) did not affect the platelet-stimulated growth of fibroblasts. The expression of 5-LOX was analyzed by reverse-transcriptase-mediated PCR (RT-PCR), Western blotting and HPLC. 5-LOX message and protein was detected in fibroblasts but not in platelets. Incubation with platelets markedly increased, already after one hour, the expression of 5-LOX in the fibroblast culture. The increased 5-LOX activity was associated with an elevated level of the 5-LOX metabolite 5-hydroxyeicosatetraenoic acid (5-HETE) reaching its maximum after 1–2 hours of co-incubation of fibroblasts and platelets. The 5-HETE production was reduced by the inhibitors DMDA, ETYA and ETI. In conclusion, this study suggests that platelet-stimulated proliferation of fibroblasts is mediated by an increased 5-LOX activity, which supports recent findings indicating a crucial role for this enzyme in proliferative disorders such as atherosclerosis.
Keywords: Fibroblasts; platelets; proliferation; 5-lipoxygenase; atherosclerosis